2019
DOI: 10.3390/ijms20246346
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Pyungwi-san against Dextran Sulfate Sodium- and Clostridium difficile-Induced Inflammatory Bowel Disease in Mice

Abstract: Several lines of evidence indicate that inflammatory bowel disease (IBD) is associated with Clostridium difficile (CD) infection as a consequence of gut dysbiosis. Currently available treatments of IBD are either not very effective or have adverse effects. Pyungwi-san (PWS), a traditional Chinese herbal formulation, has long been used to treat gastrointestinal disorders. The present study was conducted to investigate the efficacy of PWS against dextran sulfate sodium (DSS) + CD-induced IBD in mice. The animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“… Modulating metabolic profiles: adenosine, lysopc, glycocholic acid, and deoxycholic acid ↓; Regulating fecal metabolite profiles: cholic acid, α-linolenic acid, stearidonic acid, and L-tryptophan ↑ Proteobacteria↓ Bacteroidetes↑ Blautia ↑ Muribaculaceae_norank ↑ Prevotellaceae UCG001 ↑ Ruminiclostridium 9 ↑ Clostridium sensu stricto 1 ↓ Escherichia_ Shigella ↓ Enterobacter ↓ ( Zou, Shen, Chen, Zhang, & Xiao, 2020 ) Pyungwi-san Decoction (PWS) 2.5% DSS + CD ( Clostridium difficile ) for 7 d (days 0 to 6) 669.1 mg/(kg·d) for 9 d (days 2 to 6) Cecum weight, spleen weight, colonic length, body weight, colonic histology, DAI score PWS exerted a number of protective effects on DSS + CD-induced colitis, which might be mediated via restoration of a balance in gut microbial communities. Regulating tissue expression of inflammatory: IL-1β↓, IL-10 and TGF-β↑; Protecting intestinal tight junction proteins: claudin-1 and occluding ↑ Bacteroidetes ↑ Firmicutes ↓ Roseberia ↑ Bacteriodes ↑ Lactobacillus ↑ Prevotella ↑ Clostridium cluster IV ↑ A.muciniphila ↓ Prevotella ↓ Escherichia coli ↓ A.muciniphila ↓ ( Yang, Bose, Lim, & Kim, 2019 ) Qingchang Huashi Formula (QHF) Chronic colitis: 2% DSS for 7 d and distilled water for 14 d, and repeated for 3 cycles; acute colitis: 2.5% DSS for 7 d QHF [36 g/(kg·d)] was intragastric administrated 3 d prior to the DSS treatment and continued until the endpoint of experiment Body weight, DAI score, colon length, colonic histology QHF [march to the effect of 5-ASA, 50 mg/(kg·d)] and each single herb of it showed protective effect in acute and chronic colitis. Alleviating inflammation: IL-1β, IL-6 and TNF-α ↓; regulating NLRP3/IL-1β pathway; Protecting integrity of intestinal barrier: Muc2, Reg3γ, ZO-1 and Occludin ↑ Firmicutes ↑ Bacteroidetes ↓ Bifidobacterium ↑ Bacteroidales ↑ Butyrate acid ↑ Isobutyric acid ↑ Valeric acid ↑ Acetic acid ↓ 4-methylisovaleric acid ↓ ( Hu, Huang, Che, Ding, & Zhang, 2020 ) Rhubarb Peony Decoction (RPD) 2.5% DSS for 5 d (days 1 to 5) 5, 10, 20 g/(kg·d) for 14 d (days 1 to 14) Body weight, DAI score, colon length, spleen index, colonic histology Protective effect at dose-dependently which seemed ...…”
Section: Chinese Herbal Medicine For Treatment Of Experimental Colitismentioning
confidence: 99%
“… Modulating metabolic profiles: adenosine, lysopc, glycocholic acid, and deoxycholic acid ↓; Regulating fecal metabolite profiles: cholic acid, α-linolenic acid, stearidonic acid, and L-tryptophan ↑ Proteobacteria↓ Bacteroidetes↑ Blautia ↑ Muribaculaceae_norank ↑ Prevotellaceae UCG001 ↑ Ruminiclostridium 9 ↑ Clostridium sensu stricto 1 ↓ Escherichia_ Shigella ↓ Enterobacter ↓ ( Zou, Shen, Chen, Zhang, & Xiao, 2020 ) Pyungwi-san Decoction (PWS) 2.5% DSS + CD ( Clostridium difficile ) for 7 d (days 0 to 6) 669.1 mg/(kg·d) for 9 d (days 2 to 6) Cecum weight, spleen weight, colonic length, body weight, colonic histology, DAI score PWS exerted a number of protective effects on DSS + CD-induced colitis, which might be mediated via restoration of a balance in gut microbial communities. Regulating tissue expression of inflammatory: IL-1β↓, IL-10 and TGF-β↑; Protecting intestinal tight junction proteins: claudin-1 and occluding ↑ Bacteroidetes ↑ Firmicutes ↓ Roseberia ↑ Bacteriodes ↑ Lactobacillus ↑ Prevotella ↑ Clostridium cluster IV ↑ A.muciniphila ↓ Prevotella ↓ Escherichia coli ↓ A.muciniphila ↓ ( Yang, Bose, Lim, & Kim, 2019 ) Qingchang Huashi Formula (QHF) Chronic colitis: 2% DSS for 7 d and distilled water for 14 d, and repeated for 3 cycles; acute colitis: 2.5% DSS for 7 d QHF [36 g/(kg·d)] was intragastric administrated 3 d prior to the DSS treatment and continued until the endpoint of experiment Body weight, DAI score, colon length, colonic histology QHF [march to the effect of 5-ASA, 50 mg/(kg·d)] and each single herb of it showed protective effect in acute and chronic colitis. Alleviating inflammation: IL-1β, IL-6 and TNF-α ↓; regulating NLRP3/IL-1β pathway; Protecting integrity of intestinal barrier: Muc2, Reg3γ, ZO-1 and Occludin ↑ Firmicutes ↑ Bacteroidetes ↓ Bifidobacterium ↑ Bacteroidales ↑ Butyrate acid ↑ Isobutyric acid ↑ Valeric acid ↑ Acetic acid ↓ 4-methylisovaleric acid ↓ ( Hu, Huang, Che, Ding, & Zhang, 2020 ) Rhubarb Peony Decoction (RPD) 2.5% DSS for 5 d (days 1 to 5) 5, 10, 20 g/(kg·d) for 14 d (days 1 to 14) Body weight, DAI score, colon length, spleen index, colonic histology Protective effect at dose-dependently which seemed ...…”
Section: Chinese Herbal Medicine For Treatment Of Experimental Colitismentioning
confidence: 99%
“…It has also been suggested that IBD is associated with Clostridium difficile (CDD) infection, resulting from dysbiosis of the intestinal flora. In contrast, Pyungwi-san normalizes the abundance ratio of Firmicutes/Bacteroidetes in the intestine and has some protective effect against DSS + CDD-induced colitis, which may be achieved by restoring the balance of the intestinal microbial community [ 27 ].…”
Section: Intestinal Mucosal Barriermentioning
confidence: 99%
“…For H&E and AB/PAS staining of the desired tissues, the sections were placed on positively charged silicon-coated glass slides, deparaffinized with xylene and then rehydrated using a graded series of decreasing alcohol concentrations. Finally, the liver and epididymal adipose tissue sections were stained with H&E solution (Sigma-Aldrich) and the intestinal sections were stained with an alcian blue/PAS staining kit (Abcam, Cambridge, MA, USA), in accordance with previous reports [40,41]. For Oil Red O staining of the liver, the hepatic tissues were embedded in FSC 22 Frozen Section Compound (mounting medium) (Leica Biosystems, Buffalo Grove, IL, USA) and frozen at −30 • C. The tissues were then sectioned at a 12 µm thickness using a Leica CM1860 Cryostat microtome (Leica Microsystems, Nussloch, Germany).…”
Section: Histological Analysismentioning
confidence: 99%
“…The images were captured using a DP70 digital camera (Olympus) at 100×, 200× and 400× magnifications. The histological parameters, such as the diameter and area of the adipocytes in the epididymal fat tissue, as well as the number of goblet cells, crypt depth and mucus layer thickness in the intestinal tissue sections, were analyzed, as described previously [26,41] using ImageJ, a public domain Java-based image-processing software developed at the National Institutes of Health (Bethesda, MD, USA).…”
Section: Histological Analysismentioning
confidence: 99%